Formulation of Article 488 of the Indonesian Criminal Code Draft: A Portrait of Failure in Construing the Problem of Women's Access to Legal Identity - Nurtjahyo, Lidwina Inge (Jurnal Perempuan, 2018)
The Draft of the Indonesian Criminal Code has provoked a debate, especially with regard to the articles under the scope of decency. The formulation of Article 488 has the potential to create new problems for women. Especially women who have obstacles in accessing legal identity. This Article 488 is a reflection of the failure of jurists to formulate laws, in understanding women's experience in relation to their access to the right to obtain legal identity, especially in the context of relationship. The criminal law is not the answer to all problems. This paper is compiled using data obtained from field study related to the handling of cases of violence against women under customary law, carried out by the authors and the team from Legal and Community Studies Fields in 2015, 2016 and 2017 in Eastern Indonesia; as well as data on legal and non-legal text analysis. The overall method and analysis of research findings using feminist legal studies and feminist legal theories.